COVID-19 infection complicated with acute pulmonary embolism treated with percutaneous pulmonary artery thrombectomy: a case report. Issue 7 (10th June 2022) - Petrov, Ivo; Stankov, Zoran; Dobrev, Georgi; Polomski, Petar
Abstract: Background: Coronavirus disease 2019 (COVID-19) disease is a highly prothrombotic state. Deep vein thrombosis (DVT) and pulmonary embolism (PE) are observed with increased incidence in patients infected with the severe acute respiratory syndrome coronavirus 2 virus. Case summary: A 57-year-old male patient with a recent COVID-19 infection complained of leg swelling shortly after his COVID ward discharge. A few days later he was hospitalized with acute massive PE and DVT of his left leg was diagnosed. In another facility, as the first line of treatment, the PE was managed with catheter-directed therapy (CDT) using thrombus defragmentation via 5F (French) Pigtail catheter and supraselective application of 40 mg alteplase. Following the procedure, in addition, 50 mg alteplase was also applied as a 1 hour systemic infusion. Despite the haemodynamic stabilization of the patient, he remained persistently symptomatic and tachycardic. Three days later—in our institution, a second computed tomography pulmoangiography revealed massive thrombotic masses mainly in the left pulmonary artery. Successful percutaneous thrombus aspiration was conducted. The procedure was uneventful with an immediate drop of systolic pulmonary artery pressure from 68 to 47 mmHg and relief of the patient's symptoms. Discussion: In the era of the COVID-19 pandemic, physicians have to remain vigilant of its potential thrombotic complications, the most commonly observed being DVT and PE. We demonstrated the efficacy of percutaneous thrombus aspiration in a patient with acute COVID-19-associated PE, after initial CDT with thrombus defragmentation and high-dose tissue plasminogen activator was implemented with a suboptimal result.